Feasibility, acceptability and preliminary effect of a community-led HIV self-testing model among adolescent girls and young women in Rural Northern Uganda: a quasi-experimental study protocol - Olum, Ronald; Geng, Elvin H; Kitutu, Freddy E; Musoke, Philippa M (BioMed Central Ltd, 2024)
Abstract Background Adolescent girls and young women (AGYW) in sub-Saharan Africa face a disproportionately higher HIV/AIDS burden despite the global decline in incidence. Existing interventions often fail to adequately address their unique social, economic, and cultural challenges, limiting access to essential HIV/AIDS services, including HIV testing. Emerging evidence indicates that HIV self-testing, a user-friendly and confdential method, enhances HIV diagnosis and linkage to care by targeting these barriers. This study aims to assess the feasibility, acceptability, and preliminary impact of a peer-delivered, community-health worker (CHW)-facilitated HIV self-testing intervention for AGYW in Northern Uganda. Methods This mixed-methods quasi-experimental implementation science study will employ a three-fold approach. Firstly, we will conduct baseline formative qualitative research with 50 AGYW, 50 parents/partners to AGYW, 30 CHWs, 15 community leaders, and the district health ofce to inform the design of a peer-delivered CHW-facilitated HIV selftesting intervention tailored to AGYW’s needs in Northern Uganda. Secondly, we will implement a mixed-methods pilot study to assess the intervention’s feasibility and acceptability, involving 415 AGYW, 30 AGYW peer leaders, and 10 CHWs in selected parishes and villages in Omoro district, Northern Uganda. Lastly, we will evaluate the implementation outcomes and preliminary impact of the intervention on HIV self-testing rates and linkage to care by collecting and analyzing quantitative data pre- and post-intervention, laying the groundwork for a future robust randomized controlled trial. Discussion Our intervention combines CHWs and peer-led strategies to address the unique challenges of AGYW in Northern Uganda, leveraging community resilience and peer infuence. Successful completion of this project will provide a scalable model to be evaluated in a randomized trial and replicated in similar contexts. Trial registration number PACTR202404851907736. Registered with the Pan-African Clinical Trials Registry on April 22, 2024. Keywords HIV/AIDS, Self-testing, Adolescent girls, Young women, Sub-saharan Africa
Keywords: s HIV/AIDS, Self-testing, Adolescent girls, Young women, Sub-saharan Africa